2015
DOI: 10.1590/so100-720320140005179
|View full text |Cite
|
Sign up to set email alerts
|

Preservação da fertilidade e dos ovários em mulheres com tumores anexiais benignos

Abstract: ResumoOBJETIVO: Avaliar a preservação da fertilidade e dos ovários em mulheres submetidas à cirurgia por tumor anexial benigno. MÉTODOS: Para este estudo observacional com coleta prospectiva foram incluídas 206 mulheres operadas no CAISM-Unicamp de fevereiro de 2010 a janeiro de 2014. A preservação da fertilidade foi definida como tumorectomia ou anexectomia unilateral sem histerectomia em mulheres na pré-menopausa. A preservação ovariana foi considerada quando pelo menos um ovário ou parte dele foi preservado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
1
2
0
2
Order By: Relevance
“…Some studies have shown that the reduction is related to poor response to ovarian stimulation, but the sensitivity and specificity are lower compared with the AFC. 9,14 Considering the AFC as a main variable, we found in our work that a higher AFC relates to a greater number of recruited follicles, similar to the findings of Souza et al 24 Magalhães et al 28 describe that the predictive power of the AFC is substantially similar to the serum concentration of AMH, but with a higher sensitivity. 14 The data from our work are also similar to Barbakadze et al, 21 and show negative correlation between age and the AFC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some studies have shown that the reduction is related to poor response to ovarian stimulation, but the sensitivity and specificity are lower compared with the AFC. 9,14 Considering the AFC as a main variable, we found in our work that a higher AFC relates to a greater number of recruited follicles, similar to the findings of Souza et al 24 Magalhães et al 28 describe that the predictive power of the AFC is substantially similar to the serum concentration of AMH, but with a higher sensitivity. 14 The data from our work are also similar to Barbakadze et al, 21 and show negative correlation between age and the AFC.…”
Section: Discussionsupporting
confidence: 90%
“…The inverse association of a woman's age with low a ovarian reserve is largely reported in other published studies. 9,12,24 Choi et al 25 report that before the first IVF in a patient, 60% of the predicted prognostic is for the age, and 40% for other clinical factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na América Central, esse câncer ocupou a oitava posição entre os cânceres mais frequentes em mulheres no ano 2012, com uma incidência de cinco casos a cada 100 mil mulheres nas Regiões menos desenvolvidas e 9,1 casos/100 mil mulheres nas Regiões mais desenvolvidas. Na América do Sul, ocupou a sétima posição, com uma incidência de 5,8 casos/100 mil mulheres nas Regiões menos desenvolvidas e 9,1 casos/100 mil mulheres nas mais desenvolvidas 15,4 .…”
Section: Discussionunclassified
“…Segundo Souza et al 15 , aproximadamente 70% dos tumores ovarianos ocorrem em idade reprodutiva, com maior incidência entre 21 e 40 anos. No presente estudo, evidenciou-se um maior número de casos incidentes na América Latina para a faixa etária de 40 a 59 anos.…”
Section: Discussionunclassified